Ethical Issues in Building and Maintaining Coalitions -- A 10-Step Decision-Making Model for Choosing between Right and Right - Carolyn S. Wilken; Katey Walker (EDIS, 2004)
A coalition is a group of organizations and individuals working together for a common purpose. In effective coalitions, organizations share talents and resources to address the complex issues that frequently occur in human services, education, and other non-profit spheres of activity. This document is FCS9203, one of a series of publications of the Department of Family, Youth and Community Sciences, Florida Extension Services, University of Florida, UF/IFAS. First published. April 2004.